The Research Method of Edward Taylor in Economics - Giza, Wojciech (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The purpose of the analysis is to present Edward Taylor’s theory concerning the meaning of static and dynamic approaches. This Poznań economist, who advocated the approach of a research programme initiated by A. Marshall, called for a broadening of the perspective based on thinking in terms of equilibrium models with the dynamic approach. This would make it possible to answer questions prompted by those determinants that shape exogenous variables omitted in reflections based on both the model of general equilibrium and partial equilibrium.